2006
DOI: 10.2319/070605-217
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Hand-wrist Bone and Cervical Vertebral Analyses in Measuring Skeletal Maturation

Abstract: Vertebral analysis on a lateral cephalogram is as valid as the hand-wrist bone analysis with the advantage of reducing the radiation exposure of growing subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 10 publications
5
79
1
13
Order By: Relevance
“…In 1972 Lamparski 17 created the first standards of cervical vertebral maturation as related to chronological age and to skeletal maturation as observed on hand-wrist radiographs. Subsequently many authors [3][4][5][6][18][19][20][21][22][23][24] 22 demonstrated that the greatest increase in mandibular length occurred during the pubertal growth spurt and that this could be assessed during the interval between CS3 and CS4.…”
Section: Introductionmentioning
confidence: 99%
“…In 1972 Lamparski 17 created the first standards of cervical vertebral maturation as related to chronological age and to skeletal maturation as observed on hand-wrist radiographs. Subsequently many authors [3][4][5][6][18][19][20][21][22][23][24] 22 demonstrated that the greatest increase in mandibular length occurred during the pubertal growth spurt and that this could be assessed during the interval between CS3 and CS4.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the age limit for criminal liability differs in each country (2). In legal age estimation, performing hand-wrist X-rays for skeletal age prediction and the panoramic radiographs for dental age assessment are recommended (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…La clasificación de los estadios de osificación se basa en los cambios de maduración tanto en el tamaño como en la forma de las vértebras cervicales C2 a la C6 [26,27].…”
Section: Vertebras Cervicalesunclassified
“…Por tanto, evaluar el potencial de crecimiento individual y determinar el momento óptimo para iniciar un tratamiento, proporciona información esencial para la previsión de los resultados [24][25][26][27]. Por ejemplo, la corrección de la clase II esquelética, o las deficiencias en la altura de la rama mandibular, debe llevarse a cabo cuando la probabilidad de respuesta de crecimiento es alta, es decir, durante el periodo de crecimiento circumpuberal CS3 [25][26][27][28][29][30].…”
Section: Vertebras Cervicalesunclassified